(untitled) (Terr@ Plural, 2020)
The understanding that the achievement of education is as important as the occupation of a latifundio is part of a continuous construction within the social movements of the countryside, particularly, in the MST (Landless Rural Workers Movement). Thus, this paper aims to analyze Education in/of Country as a public policy in coping with the inequalities historically fierce by the city-countryside division, while resisting the educational model imposed by the agrarian bourgeoisie. The results indicate that educational policies only have meaning when thought with the subjects, and not for the subjects – especially those in the countryside, who have historically been excluded from the right to an education that was not merely presential. In this sense, Countryside Education takes an important role in the dispute of hegemony of country design, society, and human formation.